(untitled) - Atkins, Harold N. (Upper Saddle River, New Jersey, 1997)
The book provides a clear, concise introduction to civil and highway construction materials, including soils, aggregates, asphalt mixtures, portland cement concrete, and other pavement materials
Keywords: Concrete,Pavements,Road materials,Soils